Rheology of palm olein emulsions stabilized by non-ionic surfactants as potential carriers for drug delivery / Mohamed Sufian Mohd Nawi and Kausar Ahmad - Mohd Nawi, Mohamed Sufian; Ahmad, Kausar (2006)
Palm olein emulsions were prepared by homogenising the oil with varied ratios of sorbitan monolaurate (Span 20®) and polyoxyethylene 20 sorbitan monolaurate (Tween 20®). Viscosity changes of these emulsions with and without Tragacanth gum were measured. The viscosity of emulsions increased drastically with increasing ratios of Span 20/ Tween 20, and decreased with increasing shear rate, indicating shear thinning. As the ratio of Span 20/Tween 20 increased to 1: 0.4 ratio, a small amount of hysteresis was observed. Significant thixotropic behaviour was noted with the addition 0/0.01% Tragacanth gum into the oil emulsion.